Before the massive modern human dispersal into Eurasia: A 55, 000-year-old partial cranium from Manot Cave, Israel. (20th June 2020) - Weber, Gerhard W.; Hershkovitz, Israel; Gunz, Philipp; Neubauer, Simon; Ayalon, Avner; Latimer, Bruce; Bar-Matthews, Miryam; Yasur, Gal; Barzilai, Omry; May, Hila
Abstract: Genetic and archaeological models predict that African modern humans successfully colonized Eurasia between 60, 000 and 40, 000 years before present (ka), replacing all other forms of hominins. While there is good evidence for the first arrival in Eurasia around 50-45ka, the fossil record is extremely scarce with regard to earlier representatives. A partial calvaria discovered at Manot Cave (Western Galilee, Israel) dated to >55 ka by uranium–thorium dating was recently described. Since then, other findings indicated an early dispersal of modern humans out-of-Africa between 194 and 177ka (Misliya-1) or possibly even earlier at 210ka (Apidima 1), and a quite long existence of Homo sapiens in Africa (Jebel Irhoud, 300ka). While the faces of these early Homo sapiens appear quite modern, the shape of the braincase seems to lack behind, reaching the modern state only around after 35ka. Here, new data and approaches were applied to the Manot 1 calvaria. The ecto- and endocranial shape analyses based on micro-computed tomography data and a landmark-semilandmark approach using multiple reconstructions of the incomplete calvaria confirm that Manot 1 is unequivocally modern human. Its endocranial shape is markedly different from the earliest known Homo sapiens and close to the Levantine Qafzeh/Skhul assemblage (120-90ka) as well as modern humans, but still shows some deviations from both groups. The absence of other Homo sapiens fossils in the Levant between the Qafzeh/Skhul and Manot populations is not supportive for the hypothesis of a continuous occupation or the local evolution of modern humans. It suggests that Manot 1 represents a population migrating out-of-Africa and reaching the Levantine corridor during warmer and wetter climatic conditions over the Northern Sahara and the Mediterranean. Manot 1 shows that both modern humans and Neanderthals (e.g. Kebara, Amud) contemporaneously inhabited the Levant during the Middle to Upper Paleolithic interface. The endocranial shape of Manot 1 might indicate that this population had not yet fully reached the brainshape of modern humans evident after 35ka.